Kuzey Kıbrıs Türk Cumhuriyeti’nde Mesleki Eğitimde Uluslararası Akreditasyon Süreci - Çoban, Şebnem; Ünal, Cihan; İlkan, Mustafa (T.C. İstanbul Şişli Meslek Yüksekokulu, 2015)
Akreditasyon, yetkili kuruluşlar tarafından, yapılan çalışmaların belirli standartlar çerçevesinde, kalitelerinin ve güvenilirliklerinin teyit edildiğinin kanıtıdır. Bununla birlikte eğitim sektöründeki akreditasyon kuruluşlarının, güvenilirliği ve geçerliliği olup olmadığı da göz önünde bulundurulması gereken önemli bir husustur. Günümüzde artan üniversite sayısı ve rekabetten dolayı, üniversitelerin eğitim kalitelerini göstermeleri açısından, akreditasyonlar büyük önem kazanmıştır. Mesleki eğitimde akreditasyonlar, hem mesleki eğitim veren öğretim kurumlarının bireysel değerlendirme yapmalarına katkı sağlamak, hem de verilen eğitime bir standart kazandırmak açısından çok önemlidir. Bunun yanında akreditasyon veren kurumların, akreditasyon almış kurumları yıllık değerlendirmeleri, bu kurumların eğitim kalitesini hem güncellemekte hem de arttırmaktadır. KKTC’de (Kuzey Kıbrıs Türk Cumhuriyeti) mesleki eğitim veren kurumlarda akreditasyon süreci, üniversite sayısı günden güne arttığından dolayı çok büyük önem kazanmıştır. DAÜ (Doğu Akdeniz Üniversitesi), ABET (The Accreditation Board for Engineering and Technology), ASIIN (Accreditation Agency for Degree Programmes in Engineering, Informatics, Natural Sciences and Mathematics), FIBAA (Foundation for International Business Administration), ACA (The American Communication Association), AQAS (Agency for Quality Assurance through Accreditation of Study Programs), EDEXCEL (Higher National Diploma-HND-UK), gibi uluslarası geçerliliğe sahip akreditasyon kuruluşları tarafından akredite edilmiştir. Eğitim kurumlarının akreditasyonları, hem eğitim kurumuna hem de öğrencilere büyük avantajlar sağlamaktadır. Akredite edilmiş mesleki eğitim veren kurumlarda öğrenim gören öğrencilerin, standart ve yüksek kalitede eğitim aldıklarından dolayı eğitimlerine farklı bir ülkede devam etmelerine olanak sağlamaktadır. Bunun yanı sıra öğrencilere iş olanakları açısından da büyük fırsatlar yaratmaktadır.

Accreditation is proof that certain commodities are in accordance with the determined standards of quality and reliability assigned by the competent authorities. In addition to this another important issue regarding accreditation is the reliability and validity of educational institutions. In today’s world where there is an ever increasing number of universities being established, which inevitably creates competition amongst them, the acquirement of accreditation has gained even greater importance. Accreditation in vocational education and vocational training that contributes to making the individual assessment of educational institutions it is also crucial to provide a standard education. Institutions that have been accredited continue to receive annual evaluations in order to continue to improve the quality of education and its currency. Gaining accreditation for vocational educational institutions has become very important in the TRNC (Turkish Republic of Northern Cyprus) since the number of universities is increasing from day to day. EMU (Eastern Mediterranean University) has been officially accredited by the following institutions: ABET (The Accreditation Board for Engineering and Technology), ASIIN (Accreditation Agency for Degree Programmes in Engineering, Informatics, Natural Sciences and Mathematics), FIBAA (Foundation for International Business Administration), ACA (The American Communication Association), AQAS (Agency for Quality Assurance through Accreditation of Study Programs), EDEXCEL (Higher National Diplomas-HNDUK). Institutions that have been accredited provide great advantages to both the students and the educational institutions likewise. Students who are studying in accredited vocational educational institutions will have the opportunity to continue with their studies in different countries, due to the officially accredited high quality education they will have received. This also creates great job prospects for the students.
Keywords: akreditasyon; kalite; mesleki eğitim; standart